2005
DOI: 10.1079/phn2005726
|View full text |Cite
|
Sign up to set email alerts
|

AIDS, drought, and child malnutrition in southern Africa

Abstract: Objective: To investigate trends in child malnutrition in six countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 5 publications
1
37
0
Order By: Relevance
“…In this population, serious effects of drought on anthropometric indices may have been prevented by public-health measures (Hari Kumar et al, 2005). The HIV/AIDS epidemic may have further amplified the effect of drought on nutrition in countries such as those in Southern Africa (Mason et al, 2005). On the other hand, malnutrition increases the risk both of acquiring and of dying from an infectious disease.…”
Section: The Complex Linkages Between Climate Change and Malnutritionmentioning
confidence: 98%
“…In this population, serious effects of drought on anthropometric indices may have been prevented by public-health measures (Hari Kumar et al, 2005). The HIV/AIDS epidemic may have further amplified the effect of drought on nutrition in countries such as those in Southern Africa (Mason et al, 2005). On the other hand, malnutrition increases the risk both of acquiring and of dying from an infectious disease.…”
Section: The Complex Linkages Between Climate Change and Malnutritionmentioning
confidence: 98%
“…Evidence showed that socio-demographic factors such as; household's poverty and income, residence, parental occupation, parental education, maternal age, family size, overcrowding, and lack of exposure to mass media have influenced the occurrence of underfive acute malnutrition [4][5][6][7][8][9][10][11][12]. Furthermore, some behavioral or community factors including lack of maternal and child health services, of adequate and safe water supply, hygiene of caregiver and of improved environmental sanitation play their role in the occurrence of malnutrition [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of underweight children rose from 5% to 20% in Maputo (1997–2002), with similar increases in other sub-Saharan regions. Changes were much smaller during non-drought periods and in areas with lower HIV prevalence [18]. …”
Section: Hiv/aids Worsens the Nutritional Status Of Childrenmentioning
confidence: 99%
“…A study from Kenya shows that weight-for-height scores in 2000 were almost 0.3 standard deviations lower for orphans [20]. In Lesotho, almost 40% of children under four who had lost both parents were underweight, compared with 16% of non-orphans (Figure 2) [18]. …”
Section: Hiv/aids Worsens the Nutritional Status Of Childrenmentioning
confidence: 99%